Psychoanalytic aspect of "noble democracy" (in the passing of cosiderationsI of I. Witkiewicz abuot Poland and Poles) - Mołdysz, Robert (Folia Philosophica, 2004)
The problem of psychoanalytic depiction of «noble democracy» is the subject of the article. This notion deserves to be analyzed for at least two reasons: 1) it is still up-to-date and has not lost its significance; many researchers claim that the noble culture determined the «national character» of Poles; 2) the familiarity of the psychoanalytical aspect of «noble democracy» can be a starting point of a discussion about the integration of Poland with the European Union. Obtaining an answer to the question of how Poles acted in the conditions of «noble democracy» and whether this behavior can be explained in terms of psychoanalysis is the target of this publication. A work of S.I. Witkiewicz entitled Niemyte dusze [Unwashed Souls] constitutes a theoretical basis for the considerations. In this work, Witkacy acquired such a concept of a man, which makes it possible to explain the identity of a Pole and the Polish status quo. The analysis of crucial Polish problems has been made in reference to the most important category of psychoanalysis - an inferiority complex, also called a «knot of handicap». According to the author of Unwashed Souls, the «inferiority complex» constitutes the «national character» of Poles. This character became the basis of unsuccessful uprisings, partitions, etc. According to Witkacy, a Pole has misacted the «knot of handicap» from the times of «noble democracy», which has revealed itself in interpersonal relations, exaggerated pride, servility, depreciation of others, alcoholism, pseudo-intellectualism, egoism, «the smile of a fool». Anarchy and lack of discipline prevailed at the level of social organization. Thus, it should not be surprising that the Polish creative activity «definitely stands below the European average».